Unlocking the Secrets of Residential Construction: Investigating Aggregate Properties for Optimal Building Performance - Gautam, Shrijana; Awasthi, Keshab Datt; Bohara, Niraj (Journal of UTEC Engineering Management, 2024)
DOI: https://doi.org/10.36344/utecem.2024.v02i01.006The objective of this study was to find the strength of aggregates from selected three rivers and suggest to use aggregates for construction from the rivers, where better quality and strong aggregates exists. Aggregates from three selected rivers were tested for, size distribution, aggregate impact value (AIV), Los Angeles abrasion test (LAA). Natural and crushed aggregates were collected and tested for preparing the M20 grade concrete.  The mean compressive strength of the concrete made from natural aggregates at 7 and 28 days was fond as 16.72 N/mm2, 16.5 N/mm2 and 14.11N/mm2  and 26.22 N/mm2 , 24.29 N/ mm2 and 23.69 N/mm2 for Danda, Jharahi and Boulaha rivers respectively. Similarly, mean compressive strength of  concrete made from crushed aggregates at 7 and  28 day was found to be 16.06 N/mm2 , 16.43 N/mm2 and 15.16 N/mm2  and  26.29 N/mm2, 24.95 N/mm2 and 24.36 N/mm2 for Danda Jharahi and Boulaha rivers, respectively. The null hypothesis (H0) was rejected and alternative hypothesis (H1) was accepted that there exist significant difference in mean value of compressive strength among the river aggregates from selected rivers. However no interaction among the river aggregates was found as Fcalc 0.05 hence null hypothesis was accepted. The higher strength aggregates were found in Danda river whereas lower strength aggregates were found in Boulaha river.